ChemInform Abstract: Clusters [Co(As3S3)2]2‐, [Ni(As3S3)2]2‐, and [Co(en)6(μ3‐S)4 (AsS3)4]2‐ with Co—As or Ni—As Bonds: Solvothermal Syntheses and Characterizations of Thioarsenates Containing Transition‐Metal Complexes. Issue 50 (10th December 2013) - Tang, Chunying; Wang, Fang; Jiang, Wenqing; Zhang, Yong; Jia, Dingxian
Abstract In aqueous solution, Co2+ and Ni2+ ions can be coordinated not only by polyamines but also by As2S3 or AsS3 units as in (III) and (IV).